Intensidades de campos elétricos em centros cirúrgicos: um estudo in situ - Moura, Marcos Antonio Muniz de (2007)
The aim of this paper is to present a study of measurement of the intensity of electric fields in a surgery room coming from radio frequency broadcasting sources located in Curitiba, Paraná. This is a result of an increase in cellular telephony and, consequently, of its transmission towers which, along with radio and TV antennas, radio service calls, wireless networks, internet connections by means of radio waves, microwave ovens, police and firefighters radio calls, radio taxi service calls, amateur radio service, GPS, and so on, produce a kind of electromagnetic pollution “in the air”. Such pollution might cause problems for the environment as well as for people’s health and there might even be some interference concerning the technologies themselves, which might cause equipment to perform unpredictable functions. Thus, it is important to become aware of the level of the intensity of these fields, especially concerning hospitals where human lives might be in danger when they depend on equipment that is likely to fail due to the presence of these magnetic fields. The results obtained in our study are compared to those recommended by the main regulating agencies. After selecting a hospital with the greatest number of antennas around, we built an experimental setup inside a surgery room, observing the minimum distance required between the walls, between the ceiling and the floor, light equipment, and among the antennas. The set up was located 1920 cm to the front and 900 cm to the right lateral position, which served as reference for placing the GPS equipment in order to obtain geographical coordinates. The equipment used involved a selective signal receiver, a notebook with a software used to receive signals and collect data, a selective antenna and isotropic electric field measurement equipment. Eleven TV channels, 16 FM radio stations and 13 radio-based stations (cellular telephony stations) have been selected. Concerning selective measurement, the result obtained was 0,005 V/m and, when compared to the most rigorous recommendation (ONIR/Switzerland) which is 4,0 V/m, the result was 0,13% distant from the one suggested. Concerning ONIR specific band (900 & 1900), that is, GSM, our study has found 0,0068 V/m or 0,14% when compared to the results recommended by ONIR for occupational exposure and 0,17% for people’s exposure in general. Concerning medical equipment, our study has found 1,75 V/m, compared to 3 V/m, expected according to NBR/IEC60601-1-2, that is, the measured field was 58,33% lower than the one recommended. Therefore, we recommend that some actions be taken such as: adopting the Precautionary Principle, which proposes anticipated protective measures in relation to uncertainties and/or unknown risks, for using broadcasting equipment; demanding that all broadcasting facilities observe Environmental Impact Assessment Studies/EIRs – Neighboring Community Environmental Impact Studies; and, finally, performing periodical measurement of the surroundings in order to check the increase in magnetic fields from other sources which produce magnetic field pollution.